The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1002/ppap.200600159
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Pulse Frequency and Duty on the Deposition Rate in Pulsed Magnetron Sputtering

Abstract: This paper investigates the influence of pulse frequency and duty on the deposition rate during the pulsed magnetron sputtering process. Whilst deposition rates increased with duty, they also showed a very marked decrease with pulse frequency. Detailed analysis of the data implies that there is a ‘dead time’ of the order of at least 500 ns at the beginning of each pulse‐on cycle, during which negligible sputtering takes place. As pulse frequency increases, the ‘dead time’ becomes a greater proportion of the to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
12
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 21 publications
5
12
0
Order By: Relevance
“…Although significantly lower discharge currents are recorded with weaker B fields (figure 2) due to the fall in plasma density, in the case of HiPIMS this actually leads to an increase in deposition rate. In agreement with pulsed-DC sputtering, HiPIMS deposition rates decrease with pulse frequency and the argument of dead-time [18] may apply here.…”
Section: The Experimental Arrangementsupporting
confidence: 81%
See 1 more Smart Citation
“…Although significantly lower discharge currents are recorded with weaker B fields (figure 2) due to the fall in plasma density, in the case of HiPIMS this actually leads to an increase in deposition rate. In agreement with pulsed-DC sputtering, HiPIMS deposition rates decrease with pulse frequency and the argument of dead-time [18] may apply here.…”
Section: The Experimental Arrangementsupporting
confidence: 81%
“…Clearly from figure 3 the peak in the discharge voltage Vd increases only marginally (by about ~ 5% at the peak) as the B-field at the target is reduced (by  45%), however Vd values hold up significantly during the pulse as we go from BF1 to BF4. The average HiPIMS target voltages <Vd> increase from 246 to 511 V as the B-field is lowered, as shown in yiled Figure 4 also reveals lower deposition rates for higher pulsed-DC frequencies, which can be understood on the basis of the arguments proposed in [18] in that there is a dead-time (500 to 1000 ns) associated with each pulse 'on-time'. This is the formative time lag described by Anders [19].…”
Section: The Experimental Arrangementmentioning
confidence: 80%
“…The magnetron was driven in pulsed magnetron sputtering mode at 250 kHz at a duty of 50% using an Advanced Energy Pinnacle Plus power supply. This frequency (250 kHz) was found to be the lowest at which a stable discharge was obtained (previous work by the authors has shown that deposition rate decreases as pulse frequency is increased in this system [16], hence the preference to operate at lower frequencies). The power supply was operated in power regulation mode at 300 W. The operating pressure was fixed at 0.2 Pa using an argon:oxygen flow rate ratio of 2.5:1.…”
Section: Methodsmentioning
confidence: 77%
“…The growing film is bombarded by ions of appropriate energy to cause modification of its structure and properties, and the rate of arrival of the ions, and hence the degree of structural modification can be controlled by varying the pulse frequency. Also, the average power dissipated at the target decreases with increasing pulse frequency and at the start of each pulse there is a dead time during which negligible sputtering occurs and the proportion of this dead time increases with increasing pulse frequency and so the deposition rate is lower at a higher frequency [23,25]. The rate of voltage change at the target during the initial stages of the pulseon period and the maximum negative voltage attained during the pulse-on period is significantly lower at higher frequencies [25].…”
Section: Aeffect Of Pulse Power Supply Parameters On the Growth Charmentioning
confidence: 99%
“…Also, the average power dissipated at the target decreases with increasing pulse frequency and at the start of each pulse there is a dead time during which negligible sputtering occurs and the proportion of this dead time increases with increasing pulse frequency and so the deposition rate is lower at a higher frequency [23,25]. The rate of voltage change at the target during the initial stages of the pulseon period and the maximum negative voltage attained during the pulse-on period is significantly lower at higher frequencies [25]. Since sputtering rate is proportional to power and sputtering yield is proportional to target voltage, both these factors tend to lower the deposition rate at a higher frequency (Fig.…”
Section: Aeffect Of Pulse Power Supply Parameters On the Growth Charmentioning
confidence: 99%